Revision of the Palaearctic brood parasitic genus Nipponodipogon Ishikawa, 1965 of spider wasps (Hymenoptera: Pompilidae: Pepsinae) - Shimizu, Akira; Lelej, Arkady S.; Loktionov, Valery M. (Zootaxa, 2015)
The systematics and bionomics of the Palaearctic brood parasitic genus Nipponodipogon Ishikawa, 1965 are revised. Seven species are listed. A new species N. sudai Shimizu, sp. nov. (Japan, Honshu) and the hitherto unknown males of N. iwatai (Ishikawa, 1965) and N. nagasei (Ishikawa, 1965) are described and illustrated. Six species from Japan and the Russian Far East are redescribed. A key to species is provided.